2021
DOI: 10.3389/fevo.2021.734128
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Floral Scent and Petal Reflectance Between Diploid and Tetraploid Chamerion angustifolium

Abstract: Genome duplication in plants is thought to be a route to speciation due to cytotype incompatibility. However, to reduce cross-pollination between cytotypes in animal-pollinated species, distinctive floral phenotypes, which would allow pollinator-mediated assortative mating between flowers, are also expected. Chamerion angustifolium is a Holarctic species that forms a hybrid zone between diploid and tetraploid populations in the North American Rocky Mountains. Extensive research has shown that these cytotypes d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 87 publications
1
6
0
Order By: Relevance
“…The features of the reproductive organs, including inflorescence size, floral display, color, scent chemistry, and nectar quantity, can affect pollinator behavior and pollination efficiency (Husband and Schemske, 2000;Anssour et al, 2009;Balao et al, 2011). In line with the current results, both floral fragrance cues and petal reflectance changed across cytotypes of diploid and tetraploid flowers in Chamerion angustifolium (Palmqvist et al, 2021). Also, Davis et al (1994) reported that haploids of Brassica rapa yielded nectar carbohydrates three times less than those of its 2n and 4n lines, which is in general agreement with the findings of the current study.…”
Section: Discussionsupporting
confidence: 81%
“…The features of the reproductive organs, including inflorescence size, floral display, color, scent chemistry, and nectar quantity, can affect pollinator behavior and pollination efficiency (Husband and Schemske, 2000;Anssour et al, 2009;Balao et al, 2011). In line with the current results, both floral fragrance cues and petal reflectance changed across cytotypes of diploid and tetraploid flowers in Chamerion angustifolium (Palmqvist et al, 2021). Also, Davis et al (1994) reported that haploids of Brassica rapa yielded nectar carbohydrates three times less than those of its 2n and 4n lines, which is in general agreement with the findings of the current study.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, before introducing the plant into the chambers, to assess background scent level in the chambers, we collected, using the same method, blank samples, i.e., samples of air within empty chambers. Indeed, in semi-controlled experiments with whole plants, despite the fact that the air injected into the sampling chambers is purified with activated charcoal, exogenous compounds, which are considered as contaminants, are always present in the samples, and therefore must be removed from the plant samples (see methods in Palmqvist et al, 2021;Rupp et al, 2021). At the end of each O 3 exposure in the first experiment, inflorescences and leaves were cut from the plant and placed for 4 days at 40 • C in an oven to measure the dry biomass.…”
Section: Study Systemmentioning
confidence: 99%
“…Experimental work has shown different floral morphology and pollinator behaviors between natural polyploids (i.e. polyploids established in populations in the wild) and their presumed diploid progenitors, but not necessarily increased visitation of polyploids by pollinators (Segraves and Thompson 1999, Palmqvist et al 2021). However, such polyploids have undergone natural selection, and the direct effect of whole genome duplication cannot be derived from such experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, other mechanisms are likely to contribute to reproductive isolation between diploids and newly formed polyploids in early stages, such as assortative mating driven by pollinator shift. Differences in floral morphology and pollinator preference between diploids and established polyploids have been shown, leading to assortative mating (Segraves and Thompson 1999, Palmqvist et al 2021). Again, these may be explained by late‐acting selective processes rather than polyploidy itself.…”
Section: Introductionmentioning
confidence: 99%